Expression of Leadership in Practical Activities of Leader of Artistic Collective - Tavoras, Vilius; Kvedaravičiūtė, Gailė (Pedagogika, 2014)
Following the experience of Lithuanian and foreign educational researchers, this article analyses the expression of leadership in practical activities of the leader of artistic collective. The role and purpose of leadership in practical activities of the leader of artistic collective are also revealed, peculiarities of expression of leadership skills are identified and the most important strategies for development of expression of leadership skills are highlighted. The problem of the research: how practical activities may influence spread of leadership of artistic collective’s leader and what kind of influence this may be. The object of the research: leadership of artistic collective’s leader and its expression in practical activities. The aim of the research: to reveal peculiarities of expression of leadership of artistic collective leader in practical activities. The methods of research: analysis of scientific literature, description (model) of expression of leader’s skills, questionnaire survey, calculation of absolute and percentage values. Conclusions: Following the analysis of scientific literature, the leadership in this article is defined as an influence process, which is manifested in practical activities through communication and collaboration, initiative, reflectivity and personal qualities. The developed and scientifically substantiated model of expression of leadership of artistic collective’s leader consists of the following components: communication and collaboration, which is expressed through ability to work in a team; expeditious informing about the conducted activity, its situation and changes; efficient conflict resolution; initiative, which is manifested in formulation and presentation of vision and goals; organisation of activities; consistency of activities; reflectivity, which is expressed through professional development; reaction to feedback and self-assessment; personal qualities, which are realised through charisma, inspiration and determination. 1. Leadership of artistic collective’s leader are strongest revealed in practical activities through communication and collaboration (52.4 % of the leaders are able to understand importance of collaboration of collective members and 72.4 % of them understand peculiarities of socialpsychological maturity of the collective) and initiative (almost every second leader (48.2 %) is able to set high and ambitious goals to oneself and members of the collective and the majority of them (71.2 %) are frequently successful in searching for new kinds of activities and implementing them). Least frequently leadership of artistic collective’s leaders is expressed through reflectivity. Occasionally only almost half of the leaders in the research (48.6 %) succeed in analysing achievements and progress of the collectives and 45.7 % of the leaders are able to analyse causes of behavior and to react efficiently. More than third of the respondents (39.5 %) only sometimes manage to apply the principle of experiential learning: to discuss its effect on members of the collective. The revealed peculiarities of leadership skills enabled to establish the key strategies for development of expression of leadership of artistic collective’s leader: 1) deeper reflection of activities, 2) development of collaboration, 3) self-development of personal features, 4) encouragement of initiative at all the levels of activities.